On Pushkin, Cultural Continuity and Linguistic Features of Modern Media Discourse - Olga N. Savinova (Гуманитарный вектор)
The article emphasizes the enormous influence of the work of Alexander Pushkin on the entire national culture, literature and language. It became the source of the most significant socio-historical, philosophical, aesthetic ideas for all subsequent Russian literature. Personal reader observations related to the classical heritage and language of the modern media space, as well as practical experience in training journalistic personnel, prompted the author to turn to the problem of cultural continuity, which has become relevant in recent years to our society. Attention is drawn to the fact that high school graduates who have chosen the specialty of journalist and public relations specialist have in recent years come to university with a weak background of general cultural knowledge. “Digital” youth, brought up on exams, don`t always give preference to reading original literature.The purpose of the article is to understand the modern process of cultural continuity, cultural and linguistic meanings and features of modern media discourse. Society is based on communication, and communication is impossible without a common system of concepts and values. The author expresses the idea that in the context of the new challenges of our time, society has clearly formulated a request for the preservation of national roots, national culture, domestic classics, the need to preserve the intergenerational cultural code as an urgent task that determines the dynamics of the humanities in general and journalism in particular. Based on the method of theoretical analysis, as well as using the method of content analysis, the author analyzes the specific results of a study of the press of the big cities in the Privolzhskiy Federal District, the state of the modern media agenda and changes that have affected the language of modern media. The author concludes that these processes reflect the transformation of both the press and society. Also, we express an opinion on the need for attention to the issues of the mission of modern media discourse, the influence of media on the formation of the spiritual world of modern humanity, its worldview and civic position, which was characteristic of the best traditions of Russian culture.